Growth, differentiation and cell-cell coupling in the human neuroblastoma cell line SH-SY5Y. - Belbaraka, Loubaba. (University of Ottawa (Canada), 2002)
Neuroblastoma is one of the most common paediatric solid tumours, frequently occurring in infancy with the primary lesion in the adrenal gland and sympathetic nervous system. It originates from primitive neural crest cells. In rare cases, this tumour regresses spontaneously to a more benign ganglioneuroma probably by neuronal differentiation or apoptosis. We investigated the role of induction of neuronal differentiation and apoptosis in vitro in SH-SY5Y neuroblastoma cells. A variety of agents that are known to induce neuronal differentiation including retinoic acid, nerve growth factor (NGF), protein kinase C (PKC) inhibitors and a cAMP-dependent protein kinase A (PKA) activator were tested solely or in combination for their capacity to induce terminal differentiation. The cells were characterised for markers of differentiation as well as their ability to withdraw from the cell cycle. We found that the combination of 8-Br-cAMP (PKA activator) with NGF in the presence of the cell cycle inhibitor aphidicolin was the best treatment to induce terminal differentiation in SH-SY5Y cells. Treated cells showed long neurites resembling those of neurones. They expressed markers characteristic of the cytoskeleton (NF200, NF68) and of neuronal function (tyrosine hydroxylase, choline acetyltransferase and the neurone-specific enolase) and showed an increase in the expression of TrkA, the receptor for NGF. Furthermore, the expression of the N-myc oncogene that is normally overexpressed in these cells decreased. Since neurones are dependent on NGF for survival, we tested the ability of terminally differentiated SH-SY5Y cells to survive in the absence of NGF. We found that the cells became NGF-survival dependent and that deprivation from this neurotrophic factor induced programmed cell death. We also tested the effect of PKC specific and non-specific inhibitors on cell proliferation, differentiation and apoptosis in SH-SY5Y cells. We found that only the non-specific PKC inhibitors staurosporine and H7 induced morphological and molecular differentiation as well as decreased N-myc amplification followed by apoptosis. The effect of differentiation induction on p53 sub-localisation was also investigated in undifferentiated and differentiated SH-SY5Y cells. p53 immunostaining showed that p53 was sequestered in the cytoplasm in undifferentiated SH-SY5Y cells and that the induction of differentiation resulted in the partial transfer of p53 to the nucleus where it probably became able to regulate the cell cycle and apoptosis since p53 is not mutated in neuroblastoma. Gap junction intercellular communication (GJIC) is known to be involved in the regulation of cell growth and homeostasis and has been shown to contribute to many diseases including cancer. We investigated the role of GJIC in neuroblastoma. We found that SH-SY5Y cells have altered GJIC due to an aberrant localisation in the perinuclear region of connexin 43 (Cx43), one of the proteins of GJIC normally present at the plasma membrane. GJ channel formation and gating is regulated by PKC, PKA and/or MAPK. We found that induction of differentiation using the PKA activator 8-Br-cAMP relocalised Cx43 to the plasma membrane region and restored GJIC. Furthermore, inhibition of p38 MAPK induced a block of cell proliferation associated with GJIC proficiency while inhibition of the subfamily of MAPK, Erk1/Erk2, likely promoted the degradation of Cx43.
Keywords: Biology, Cell.